THE EFFECTIVENESS OF EDAMAME (GLYCINE MAX(L.) MERRILL) EXTRACT AS ACRYLIC RESIN DENTURE CLEANSER ON THE NUMBER OF CANDIDA ALBICANS - Kristiana, Dewi; Hidayati, Lusi; Nabil, Humam Rafif (Odonto : Dental Journal, 2022)
Background: Cleaning in denture base is needed to reduce the Candida albicans colonization and prevent denture stomatitis. Denture cleaning can be mechanically cleaned with a toothbrush, or chemically cleaned by immersion. Another natural ingredient that can be used for immersion is edamame (Glycine max (L.) Merrill) extract because it contains saponins, which contain antifungal compounds that can inhibit C. albicans. The purpose of this study was to determine the effectiveness of edamame extract (Glycine max (L.) Merrill) as a heat-cured acrylic resin denture cleanser with concentrations of 25%, 50%, 75%, and 100% by soaking for 8 hours against the amount of C. albicans. Method: This research is a laboratory experimental study with 50 samples divided into 5 groups. The research group consisted of immersion acrylic resin samples with C. albicans contamination for 8 hours in the control group, namely sterile distilled water and the treatment group, namely edamame extract with concentraions of 25%, 50%, 75%, 100% and then spectrophotometer test to see the absorbance of C. albicans.Result: The ANOVA test result showed p <0.005 Based on the results of the LSD test, it showed that there was a significant difference (p<0.05) in most groups except the control group against the acrylic group soaked in 25% edamame extract and acrylic soaked in 75% edamame extract against the acrylic group soaked in 50% and 100% of edamame extractConclusion: Edamame extract at 100% concentration as acrylic resin denture cleanser was the most effective in reducing the amount of C. albicans by soaking for 8 hours